Measuring the determinants of real estate investment trusts (REITS) performance: Malaysian evidence - Chang, Fei Yong; Mohd Thas Thaker, Hassanudin; Mohd Thas Thaker, Mohamed Asmy; Allah Pitchay, Anwar (Universiti Malaysia Sabah, 2017)
The objective of this research is to study the relationship between firm-specific variables (diversification on property type and location, size of company, cost of capital, and underlying property income – model one) and macroeconomic variables (gross domestic product, interest rate, and exchange rate – model two) with the performance of real estate investment trusts (REITs) in Malaysia during the period of 2011 to 2015. The rate of return is used to measure the performance of REITs in Malaysia. This study adopted correlation and regression analysis, and thus, concluded that diversification on property type, size of firm and underlying property income are significant in this research; while all of the macroeconomic variables are insignificant. With the potential of the REITs, it is expected that this research provides insight on M-REITs’ performances to companies, future investors, investment brokers, and other researchers who study the M-REITs market.